Diversity Bears Fruit: Evaluating the Economic Potential of Undervalued Fruits for an Agroecological Restoration Approach in the Peruvian Amazon - Lagneaux, E.; Jansen, M.; Quaedvlieg, J.; Zuidema, Pieter A.; Anten, N.P.R.; García Roca, M.R.; Corvera Gomringer, Ronald; Kettle, Christopher J. (MDPI, 2021)
Agroforestry systems with a range of native and often neglected and underutilized tree species (NUS) are increasingly recognized for their potential role in restoration, simultaneously providing ecological and livelihood benefits. Successful adoption of these systems requires knowledge about beneficial species, system-level potential profitability, and barriers faced by farmers. Such information is essential but lacking for most NUS. We analyzed the economic potential of NUS in diverse smallholder-managed agroforestry systems in the Peruvian Amazon. Through semi-structured surveys with local stakeholders (n = 40), we identified 10 native Amazonian NUS fruit with ecological, nutritious and commercial benefits. We then simulated the potential revenue per species and system-level profit of an agroforestry system designed with the 10 NUS. Our projections suggest that a diverse NUS-based agroforestry system can outcompete most alternative land-uses in the region on a per hectare profit basis. This shows that including NUS in restoration efforts could provide economic benefits for smallholders. To realize this potential, we recommend adapted interventions, e.g., increased farmer access to planting material, technical support for production and capacity building with a focus on high-potential NUS.